2021
DOI: 10.22541/au.161865246.65161792/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone acetylation regulates the expression of genes involved in worker reproduction and lifespan in the ant Temnothorax rugatulus

Abstract: In insect societies, the queen monopolizes reproduction while workers perform tasks such as brood care or foraging. Queen loss leads to ovary development and lifespan extension in workers from many ants. However, the underlying molecular mechanisms of this phenotypic plasticity remain unclear. Recent studies highlight the importance of epigenetics in regulating plastic traits in social insects. We investigated the role of histone acetylation in the regulation of worker reproduction in the ant Temnothorax rugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Functional enrichment analyses for the formicoid branch revealed that histone acetylation was the most significantly over-represented function among the 110 positively selected genes. Histone acetylation is well-known for controlling transcriptional activity 23 , reprograming foraging behaviour of the major worker caste into the minor worker caste 24 , colony activity rhythms 25 , and the longevity/fecundity trade-off in workers 26 . Histone acetylation is also involved in caste determination of honeybees through the effect of royal jelly 27 and has been identified as a key caste-specific enhancer of transcription regulating the differential larval development of queens and workers 28 .…”
Section: Pervasive Positive Selection Associated With the Origin Of T...mentioning
confidence: 99%
“…Functional enrichment analyses for the formicoid branch revealed that histone acetylation was the most significantly over-represented function among the 110 positively selected genes. Histone acetylation is well-known for controlling transcriptional activity 23 , reprograming foraging behaviour of the major worker caste into the minor worker caste 24 , colony activity rhythms 25 , and the longevity/fecundity trade-off in workers 26 . Histone acetylation is also involved in caste determination of honeybees through the effect of royal jelly 27 and has been identified as a key caste-specific enhancer of transcription regulating the differential larval development of queens and workers 28 .…”
Section: Pervasive Positive Selection Associated With the Origin Of T...mentioning
confidence: 99%
“…Queenless workers in other ants were also typically longer lived or more stress resistant than workers with queen (Majoe et al, 2021;Choppin, 2022;, possibly because molecular pathways for egg production also affect body maintenance. For instance, the egg yolk precursor vitellogenin protects honeybee workers from oxidative stress (Münch & Amdam, 2010).…”
Section: Queen Loss Does Not Affect Worker Survival and Fat Body Tran...mentioning
confidence: 99%